2021
DOI: 10.1007/s11250-020-02491-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LPS and LTA stimulation on the expression of TLR-pathway genes in PBMCs of Akkaraman lambs in vivo

Abstract: This is the first study investigating the changes in some gene expressions related to the TLR pathway in vivo in sheep. Lipopolysaccharide (LPS) and lipoteichoic acid (LTA) molecules were administrated separately and in combination to the Akkaraman lambs via intranasal route. For this purpose, 28 lambs were distributed into four groups (LPS, LTA, LPS + LTA, and control, n = 7). Blood samples were collected to isolate the peripheral blood mononuclear cells (PBMCs) at 24 h and on day 7. Expression levels of TLR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Although the TLR4 gene displays an orthology relationship across species (Roach et al, 2005), our transcriptomic profiles indicated that the LPS-stimulated gene expression, cytokine production and biological response were different to some extent. PBMCs activated by LPS lead to the innate immunity activation of monocytes and dendritic cells, featuring the inflammatory program mediated by NF-κB and interferon gene expression mediated by IRFs (Aksel and Akyüz, 2021). In our DEGs analyses, we observed that the NFKB1 showed increased expression across all four species, and NFKB2 was consistently upregulated in giant pandas, humans, and mice.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although the TLR4 gene displays an orthology relationship across species (Roach et al, 2005), our transcriptomic profiles indicated that the LPS-stimulated gene expression, cytokine production and biological response were different to some extent. PBMCs activated by LPS lead to the innate immunity activation of monocytes and dendritic cells, featuring the inflammatory program mediated by NF-κB and interferon gene expression mediated by IRFs (Aksel and Akyüz, 2021). In our DEGs analyses, we observed that the NFKB1 showed increased expression across all four species, and NFKB2 was consistently upregulated in giant pandas, humans, and mice.…”
Section: Discussionmentioning
confidence: 65%
“…Several in vitro and in vivo studies about LPS-stimulated PBMCs were performed on different animals (e.g., chickens and lambs) followed by qRT-PCR to understand the changes of certain gene expressions (Aksel and Akyüz, 2021;Slawinska et al, 2021). However, the number of tested genes was limited.…”
Section: Introductionmentioning
confidence: 99%
“…There are many in vivo and in vitro studies examining the effect of LPS and LTA induction on the immune response in various tissues of humans and mammals (goat, cattle, sheep, and mouse) (Hillman et al, 2008; Ibeagha-Awemu et al, 2008; Deng et al, 2012; Rashidi et al, 2015; Bulgari et al, 2017; Wei et al, 2019; Sánchez-Tarjuelo et al, 2020; Aksel & Akyüz, 2021). A study examining the antigenic effects of LPS and LTA in goat mammary epithelial cell culture determined that LTA induced a weaker inflammatory response than LPS, and TLR4 gene expression level was higher in the treatment groups compared to the control group 6 h after LPS and LTA applications (Bulgari et al, 2017).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Another study concluded that LPS administration increased TLR4 expression level in fetal sheep lung cells (Hillman et al, 2008). The blood samples taken 24 h after the LPS, LTA, and LPS + LTA administration in Akkaraman lambs showed that the TLR4 gene expression level was higher in the LTA + LPS group than in the control and LTA groups (Aksel & Akyüz, 2021). Wei et al (2019) reported that TLR4 gene expression increased in peripheral blood cells following in vitro LPS administration in sheep.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Notably, even with this characteristically low toxicity, Caulobacter remains capable of stimulating an innate immune response, supporting its potential as an adjuvant [ 378 ]. LPS has been shown to activate the complement system to increase C5a as well as interact with immune cells via TLR-4 [ 19 , 26 ], both stimulating the NF-κB pathway [ 379 ] to release inflammatory cytokines such as IL-1, IL-6, IL-8, TNF-α, and IFN-γ, and to recruit immune cells for an adaptive immune response ( Figure 2 ). Safety is a crucial aspect in developing oncolytic bacteria for clinical application, which, particularly when paired with the homogenous nature of the S-layer, makes C. crescentus an excellent candidate for engineering to generate further prophylactic capacities.…”
Section: Prophylactic Bacteriamentioning
confidence: 99%